2016
DOI: 10.1002/ppap.201600172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate outgassing on the plasma properties during wood treatment in He dielectric barrier discharges at atmospheric pressure

Abstract: This work analyzes the effect of wood outgassing on the properties of He dielectric barrier discharges operated in a homogenous regime. Over the 60 min wood treatment investigated, the discharge current increased by almost a factor of two due to the release of air and humidity. Based on optical emission spectroscopy and collisional-radiative modeling, these effects further yield to an increase of the electron temperature and a significant decrease of the relative number density of He metastable atoms. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
6
12
0
Order By: Relevance
“…This latter difference with the jet configuration can most likely be attributed to the presence of N2 and O2 due to open-air configuration; this aspect was already discussed by Levasseur et al in He-based discharges. [29] The same Ar-NH3 jet study also reported Ar metastable number densities in the range of 10 11 and 10 12 cm -3 , which is in agreement with the values obtained in this work and those expected for glow dielectric barrier discharges (10 11 cm -3 ). [14,28] Another study reported argon atom metastable densities of 4.10 13 cm -3 in an Ar-NH3 discharge powered with 1.2 W.cm -3 at 15 kHz, which is 100 times higher than the values obtained in this study using similar dissipated volume powers (1.5 W.cm -3 with the 35 kHz, 1 mm) [30].This increase likely comes from a difference in the discharge regime since the large current peak duration (25 µs) reported by this group indicates the behavior of a Townsend discharge, which is known to be characterized by much higher metastable number densities [14].…”
Section: Discussionsupporting
confidence: 90%
“…This latter difference with the jet configuration can most likely be attributed to the presence of N2 and O2 due to open-air configuration; this aspect was already discussed by Levasseur et al in He-based discharges. [29] The same Ar-NH3 jet study also reported Ar metastable number densities in the range of 10 11 and 10 12 cm -3 , which is in agreement with the values obtained in this work and those expected for glow dielectric barrier discharges (10 11 cm -3 ). [14,28] Another study reported argon atom metastable densities of 4.10 13 cm -3 in an Ar-NH3 discharge powered with 1.2 W.cm -3 at 15 kHz, which is 100 times higher than the values obtained in this study using similar dissipated volume powers (1.5 W.cm -3 with the 35 kHz, 1 mm) [30].This increase likely comes from a difference in the discharge regime since the large current peak duration (25 µs) reported by this group indicates the behavior of a Townsend discharge, which is known to be characterized by much higher metastable number densities [14].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, in these conditions, Te and n(Arm) thus vary by compensating one another. A similar behavior was previously reported for helium DBDs [9,33] and argon-ammonia discharges [10,24]. Figure 5.…”
Section: Variation Of the Electron Temperature And The Argon Metastabsupporting
confidence: 86%
“…In addition, it is well established that the deposition rate of SiOCH coatings in He/HMDSO plasmas is larger than the deposition rate of SiO x coatings in He/HMDSO/O 2 plasmas. [ 60 ] Therefore, considering substrate outgassing phenomena, the thickness of plasma‐deposited coatings is expected to be larger near the entrance than near the exit, as observed in Figure 5c.…”
Section: Resultsmentioning
confidence: 99%